ON CLASSICAL CEPHEIDS' PERIODS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
The Fourier analyses performed for photoelectric Berdnikov’s (1992) V-observations of seven classical Cepheids give periods (frequencies) and amplitudes their oscillations as well as their harmonics (from one to six for different stars).